STUDI EKSPERIMENTAL NANOREFRIGERAN TiO2-R600a SEBAGAI REFRIGERAN MASA DEPAN - Rozaq, Abdur; Siddiq, Nur Abdillah; Putra, Rendy Krisnanta; Yusuf Z, Muhammad Dicky; Muyasaroh, Siti (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
The use of CFC refrigerants (Chloro Fluoro Carbon) leads to destruction of ozone layer and global warming. An alternative refrigerant is hydrocarbon refrigerant, but it has the disadvantage of easily exploded. This experimental study has been conducted to study the effect of addition of TiO2, which are flame retardant, on the performance of hydrocarbon refrigerant R600a (nanorefrigeran TiO2-R600a). Test of Performance conducted according to refrigerants national standards IEC 60335-2-24-2010. The result is R600a-TiO2 is safe and efficient to be used as a refrigerant without any modification on refrigerator. TiO2 increases the thermal conductivity and heat transfer of refrigerant. The best performance is obtained at TiO2 concentration of 1 g / L (COP = 4,821). It is expected that the nanorefrigeran TiO2-R600a can be used as the primary refrigerant in the future that are environmentally friendly and efficient.Â Keywords: Â Nano-Refrigerant, R600A, TiO2, COP